SPECIFICITY OF THE RESPONSE OF THE BODY OF CHILDREN WITH MOTOR LIMITATIONS AND CEREBRAL PALSY WHEN PERFORMING ACTIVE PHYSICAL EXERCISES USING EXERCISE EQUIPMENT - Gross N.A.; Sharova T.L.; Molokanov A.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the features of functional adaptation of the body of children with cerebral palsy when performing physical activity using exercise equipment in rehabilitation sessions. Methods and structure of the study. The study involved children with cerebral palsy of primary school age. Exercise machines and other methods of physical exercise included in the rehabilitation session were used. Heart rate (HR) (a total of 211 observations) was measured using a Polar RS 800 chest heart rate monitor continuously during one session. Results and conclusions. The highest average HR values ​​were found in children of GMFSC level III in seven (out of eight) types of physical activity. The highest average HR results were shown in "Jumps" in children of all levels: in children of levels I-II (135±13.3 bpm), level III (142±14.6 bpm), performed independently or with the help of the "Gross Simulator", in the group of levels IV-V - (139±8.2 bpm), performed only in the "Gross Simulator". The maximum indicators from the ranges of HR values ​​were noted in the group of children of levels I and II - (166 - 85) bpm. The highest HR values ​​were noted in the physical activity in children of level III "Jumps independently or in the Gross Simulator" 142±14.6 bpm and on the "Ellipse Simulator" – 134±5.2 bpm; in children of I and II levels "Walking on knees in the "Gross Trainer" – 138±8.7 beats/min; work. The results of the experiment open up prospects for understanding the processes of functioning of the body of a disabled child when using training devices. They can become a guideline for taking into account the sequence of arrangement of "Training devices" in order to avoid overtraining of the child’s body, for the accumulation of data characterizing the functional response to physical activity using training devices.